Design and methods of a longitudinal study investigating the impact of antiretroviral treatment on the partnerships and sexual behaviour of HIV-infected individuals in rural KwaZulu-Natal, South Africa - Richter Linda; McGrath Nuala; Newell Marie-Louise (BMC, 2011)
Abstract Background Diagnosed HIV-infected people form an increasingly large sub-population in South Africa, one that will continue to grow with widely promoted HIV testing and greater availability of antiretroviral therapy (ART). For HIV prevention and support, understanding the impact of long-term ART on family and sexual relationships is a health research priority. This includes improving the availability of longitudinal demographic and health data on HIV-infected individuals who have accessed ART services but who are not yet ART-eligible. Design and methods The aim of the study is to investigate the impact of ART on family and partner relationships, and sexual behaviour of HIV-infected individuals accessing a public HIV treatment and care programme in rural South Africa. HIV-infected men and women aged 18 years or older attending three clinics are screened. Those people initiating ART because they meet the criteria of WHO stage 4 or CD4 ≤ 200 cells/μL are assigned to an 'ART initiator' group. A 'Monitoring' group is composed of people whose most recent CD4 count was >500 cells/μL and are therefore, not yet eligible for ART. During the four-year study, data on both groups is collected every 6 months during clinic visits, or where necessary by home visits or phone. Detailed information is collected on social, demographic and health characteristics including living arrangements, past and current partnerships, sexual behaviour, HIV testing and disclosure, stigma, self-efficacy, quality of family and partner relationships, fertility and fertility intentions, ART knowledge and attitudes, and gender norms. Recruitment for both groups started in January 2009. As of October 2010, 600 participants have been enrolled; 386 in the ART initiator group (141, 37% male) and 214 in the Monitoring group (31, 14% male). Recruitment remains open for the Monitoring group. Discussion The data collected in this study will provide valuable information for measuring the impact of ART on sexual behaviour, and for the planning and delivery of appropriate interventions to promote family and partner support, and safe sexual behaviour for people living with HIV in this setting and elsewhere in sub-Saharan Africa.